Relationship Between Skin Scales and the Main Flow Field Around the Shortfin Mako Shark Isurus oxyrinchus - Zhang, Chengchun; Gao, Meihong; Liu, Guangyuan; Zheng, Yihua; Xue, Chen; Shen, Chun (Frontiers in Bioengineering and Biotechnology, 2022)
The aim of this study is to reveal potential relationship between the main flow field around a shortfin mako shark and surface morphology of shark skin. Firstly, numerical simulation using large eddy simulation (LES) method is conducted to obtain the main flow field around a smooth shark model. Then, the surface morphology characteristics of a shark (Lamna nasus) at different positions are characterized by scanning electron microscope (SEM). SEM images show that the morphology, riblet size, and density of scales on different positions of the shark are significantly different. At the positions (i.e., nose and leading edge of fins) where the shark faces a water flow direction, the scales are flat and round, with a lower density, and the pressure or wall shear stress (WSS) is greater. Scales with three longitudinal riblets ending in three tips are found in the middle and trailing edge of the first dorsal fin and caudal fin, where the flow states progress from transitional to turbulent. The range of RD/RS for the anterior zone, middle zone and posterior zone of the shark is 0.05 - 0.17, 0.08 - 0.23, 0.32 - 0.33, respectively. The riblet angle is generally along the flow direction, but it varies in different areas of the shark body. The turbulence intensity increases gradually on the first dorsal fin, pectoral fin, caudal fin, and shark body. In summary, it is found that the microstructure riblets on the shark skin surface, always mentioned as the drag reduction structure, only locate in the transitional and turbulent regions at the middle and trailing edge of shark body and fin surfaces, and there are almost no microstructure grooves in the laminar flow region at the leading edge. This founding will provide potential design guidance for the engineering application of bionic riblet surface. The riblets place in the turbulent transition region and fully region can achieve more effective drag reduction. The riblet direction should be consistent with the flow direction.